PENGEMBANGAN MODEL PEMBELAJARAN IPS BERBASIS NILAI-NILAI KEARIFAN LOKAL TRADISI KEBO-KEBOAN UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN SOSIAL - Rosidi, Moh. Imron; Sariyatun, S; Waluyo, Herman J. (HISTORIKA, 2014)
Â Â Â Â Â Â Â Â Â Â Â  The objectives of this research and development are (1) to describe model of Social Science learning in Bedewang Elementary State School 1, songgon district, (2) to describe the development of Social Science learning based on local wisdom â€œkebo-keboanâ€ tradition which increase the study result and studentsâ€™ social skill in Bedewang Elementary State School 1, Songgon District, (3) to describe the effectiveness of Social Science learning model based on local wisdom â€œkebo-keboanâ€ tradition to increase the study result and studentsâ€™ social skill in Bedewang Elementary State School 1, Songgon District.Â Â Â Â Â Â Â Â Â Â Â  The research and development is modified from Borg and Gall concept. The instruments use to collect the data are observation, interview, questionnaire, and pre test. The method used in the research consist of previous study, learning model development, and effectiveness test model. The data analysis to test the validity model uses Liker Scale with range 5, while the effectiveness test model uses t test.Â Â Â Â Â Â Â Â Â Â Â  The result of the study shows that in teaching social science teacher still focuses on conventional model, unsupported by innovative teaching model. Beside, teacher lacks ability to integrate the material and local wisdom around the students. The steps taken to develop this model are divided into several phases, they are preparation, implementation, and closing. The validation by the expert also become consideration to perfect the developed model at trial phase. The result of validation test model score is 4,22 (good), lesson plan validation score is 4,4 (good), questionsâ€™ validation score is 4,09 (good) and material validation is 4,05 (good). This model is worthy to use as the model of social science learning. The result of effectiveness shows that t test 2,578 with significance 0,0013 < 0,025 which means it can influence the social skill as many as 5,944 with significant degree 0,000 < 0,025. In other words, the social science model developed is effective to increase the study result and studentsâ€™ social skill.